2016
DOI: 10.1016/j.humov.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The coordinated movement of the spine and pelvis during running

Abstract: 20Previous research into running has demonstrated consistent patterns in pelvic, lumbar and 21 thoracic motions between different human runners. However, to date, there has been limited 22 attempt to explain why observed coordination patterns emerge and how they may relate to 23 centre of mass (CoM) motion. In this study, kinematic data were collected from the thorax, 24 lumbar spine, pelvis and lower limbs during over ground running in n=28 participants. These

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 25 publications
(3 reference statements)
1
45
1
Order By: Relevance
“…Since this measure is directed anteroposteriorly, it could reflect intermittency or alternate decelerations and accelerations corresponding to braking and propulsive forces, analogous to alternately applying "gas-brake-gas" while driving a car. The trunk muscles could be compensating for this instability since they play a critical role by eccentrically contracting to decelerate lumbopelvic motion anteroposteriorly during running (35,38). Electromyography assessment evaluating relationships among muscle activity, stability, and economy would help elucidate on the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this measure is directed anteroposteriorly, it could reflect intermittency or alternate decelerations and accelerations corresponding to braking and propulsive forces, analogous to alternately applying "gas-brake-gas" while driving a car. The trunk muscles could be compensating for this instability since they play a critical role by eccentrically contracting to decelerate lumbopelvic motion anteroposteriorly during running (35,38). Electromyography assessment evaluating relationships among muscle activity, stability, and economy would help elucidate on the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Vertically, this is plausible since runners with poor economy often demonstrate larger vertical oscillation of the pelvis (12) and CoM (12,46,51), which may translate to larger vertical accelerations. Horizontally, this is plausible since coordination patterns of the pelvis and spinal segments during running function to minimize both ML and AP changes in momentum (35,38). Indeed, Folland et al (12) recently found that runners with greater minimum AP horizontal velocity of the pelvis, i.e., more deceleration/braking were more energetically costly.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lower limb, pelvis and trunk segments were modelled and tracked using the approach described in Preece et al [9]. In addition, markers were placed on the acromion processes, lateral shoulders, medial and lateral epicondyles of the humeri, styloid processes of the ulnae and radii, as well as on the 2nd and 5th metacarpal heads.…”
Section: Methodsmentioning
confidence: 99%
“…The full-body model comprised of 16 segments, those in the reduced model, as well as the upper arms, forearms, hands and head. Data processing methods as outlined in Preece et al [9] were used, in which raw marker data were first low pass filtered (10Hz). A kinematic approach [11] was then used to define gait events for 10 consecutive gait cycles and CoM trajectories calculated using the Visual3D software.…”
Section: Methodsmentioning
confidence: 99%